The Prevalence of High Risk of Obstructive Sleep Apnea and its Association with Sociodemographic Factors among Adults in Taman Dato’ Rashid Salleh, Indera Mahkota, Kuantan - Ramli, Rawahah Husna; Hassan, Artika; Abd Rahman, Jamalludin; Mohd Rus, Razman; Pasi, Hafizah; Nasreen, Hashima E.; Abd. Aziz, Karimah Hanim; Zubir, Muhammad (IIUM Medical Journal Malaysia, 2020)
Introduction: Obstructive sleep apnea (OSA) is an insidious sleep breathing disorder, with cardinal manifestations of snoring, witnessed breathing pause during sleep and excessive daytime sleepiness. The aim of the study was to estimate the prevalence of OSA and its associated factors among adult population in Taman Dato’ Rashid Salleh, Kuantan. Materials and method: A cross-sectional study was carried out among 157 participants who lived in Taman Dato’ Rashid Salleh from May 2018 to June 2018. Obstructive sleep apnea was quantified using the self-administered Malaynvalidated Berlin questionnaire which apart from the demographic data included three categories (10 questions) designed to elicit information regarding snoring (category 1), daytime somnolence (category 2) and the presence of obesity and/or hypertension (category 3). The respondents were considered as high risk of OSA if two or more categories were positive. Weight, height and neck circumference were measured by using Secca© weight scales, Secca© stadiometer and non-elastic plastic tape, respectively. Descriptive statistics was used to measure the prevalence, while chi-square test was used to explore the association of OSA and its background variables. Results: Out of 157 respondents, female and Malay were dominant with the 56.7% and 91.0 %, respectively. The mean age of the respondents was 36.7 (12.2) years old. The prevalence of high risk of OSA in was 18.5%. There was no association between gender, age, race, smoking and neck circumference with risk of OSA while Body Mass Index (BMI) and hypertension were significantly related to an increased risk for developing OSA (p-value < 0.001 and p=0.001, respectively). Conclusions: Two in every 10 adults in Taman Dato’ Rashid Salleh, Kuantan were at high risk of OSA. It is recommended that appropriate health promotion should be targeted to this community to instill awareness and increase the level of understanding of the public on OSA.